Realism, caricature, and bias : the fiction of Mendele Mocher Sefarim - Aberbach, David, 1953- (London, UK : Littman Library of Jewish Civilization, 2008)
Explores the psychology of prejudice and self-hate in the fiction of Mendele Mocher Sefarim, one of the key figures in modern Yiddish and Hebrew literature. The book presents an analysis of the tension between realism and caricature in Mendele's portrayal of the Russian Jews under tsarist rule.
Includes bibliographical references (pages 115-122) and index.
PDF (JSTOR, viewed June 18, 2018).
JSTOR
Keywords: Mendele Mokher Sefarim, -- 1835-1917 -- Criticism and interpretation; Mendele Mokher Sefarim, -- 1835-1917 -- Psychology; Mendele Mokher Sefarim, -- 1835-1917; Mendele -- Moicher Sforim; Self-hate (Psychology); Antisemitism -- Psychological aspects; Jews -- Russia -- Psychology; Jews in literature; Autodépréciation.; Antisémitisme -- Aspect psychologique; Juifs -- Russie -- Psychologie; Juifs dans la littérature.; Antisemitism -- Psychological aspects; Jews in literature; Jews -- Psychology; Psychology; Self-hate (Psychology); Russia; Hebreeuws; Jiddisch; Criticism, interpretation, etc